Of butter knives, juice boxes, and turning points : accounts of domestic violence on two sides of the Atlantic - Kenney, Greta (Department of Sociology, 2015)
This qualitative comparative analysis examines the experience of being in an abusive relationship as well as of leaving it from the perspective of domestic violence survivors and their service providers. This work demonstrates the inadequacies of analysing domestic violence as solely an individual problem or merely as a structural issue. Instead, I argue for a comprehensive approach to understanding women’s experiences with intimate family abuse by acknowledging the complexities of how external factors explicitly inform a person’s internal process when navigating an abusive relationship.